Effects of Cr Content on Microstructure and Mechanical Properties of AlCoCrxFeNi High-Entropy Alloy - Tao-Tsung Shun; Wei-Jhe Hung (Advances in Materials Science and Engineering)
In this study, we investigated the effects of Cr content on the crystal structure, microstructure, and mechanical properties of four AlCoCrxFeNi (x = 0.3, 0.5, 0.7, and 1.0, in molar ratio) high-entropy alloys. AlCoCr0.3FeNi alloy contains duplex phases, which are ordered BCC phase and FCC phase. As the Cr content increases to x = 1.0, the FCC phase disappears and the microstructure exhibits a spinodal structure formed by a BCC phase and an ordered BCC phase. This result indicates that Cr is a BCC former in AlCoCrxFeNi alloys. With increasing Cr content, the alloy hardness increases from HV415 to HV498. AlCoCr0.3FeNi, AlCoCr0.5FeNi, and AlCoCr0.7FeNi exhibit a high compressive fracture strain of about 0.24 because of the formation of the FCC phase in the BCC matrix. Moreover, the highest yield stress of 1394 MPa and compressive strength of 1841 MPa presented by AlCoCrFeNi alloy are due to the existence of a nano-net-like spinodal structure.